The passeggiata and popular culture in an Italian town : folklore and the performance of modernity - Del Negro, Giovanna (McGill-Queen's University Press, 2004)
"[A]n evocative account of social life in the central Italian town of Sasso. Focusing on the passeggiata (ritual promenade), Del Negro provides a vivid picture of dressing, walking, courting, and socializing in Sasso's piazza."--Jacket